I am asking about a passage in the book


please see page 203.

My question is, suppose we have a PDE $$u' + Au = f$$ that we solve by using the Galerkin method. The Galerkin approximation satisfies $$(u_n', w_j) + (Au_n, w_j) = (f,w_j)\tag{1}$$ for $j=1,...,n$, where $w_j$ is the basis. According to this book, we can write this as $$u_n' + Au_n = f\tag{2}$$ but what space is this an equality in? The book seems to suggest $L^2(0,T;V')$, but (1) only holds for the basis functions and hence I can only see the equality holds for $L^2(0,T;V_n')$, where $V_n$ is the span of the first $n$ basis functions.

And then, the author gets an uniform estimate on $\lVert u_n'\rVert_{L^2(0,T;V')}$ by using the fact that $f, Au_n \in L^2(0,T;V')).$ I understand this follows if the equality (2) were to hold in $L^2(0,T;V')$ but if it only holds in $L^2(0,T;V_n')$ does it follow?

I posted a thread about something similar to this previously but I think this is clearer.


There is no problem in understand equality $(2)$ as an equality in $V'$, in fact remember that $V\subset H\subset V'$ is a Hilbert triple.

If I got the right notation in the book, there they consider $A=-\Delta$, $V=H_0^1$ and $H=L^2$. Now, in one hand, as I have said in first paragraph, $u'_n\in V\subset V'$. On other hand $Au_n\in H\subset V'$, so you can see the equality in $V'$.

Remark: We want to solve the equation $$u'+Au=f\tag{1}$$

Let $P_n$ be the projection onto $V_n$ and applies it in both sides of $(1)$: $$\tag{2} P_nu'+P_n Au=P_nf$$

If we write $u$ in terms of the eigenvector of $A=-\Delta$, i.e $u=\sum \lambda_k w_k$, then $P_nAu=Au_n$ where $u_n=\sum_{k=1}^n\lambda_ kw_k$, hence $(2)$ is equivalently to $$\tag{3} u'_n+Au_n=f_n$$

where $f_n=P_N f$ and $(3)$ is your equation $(1)$. Now you can note that if you solve your equation in $V'_n$, then the same equation is true in $V'$. This is because if you take any elment in $v\in V$ that belongs to $\operatorname{span}\{w_{n+1},...\}$, you have that $$\tag{4}(P_n u',v)=(P_n Au,v)=(P_n f,v)=0$$

Remark 2: I'm gonna show here that $(1)$ of Op is equivalently of my $(2)$.

I - $(1)$ implies $(2)$

Note that $(1)$ implies $$\tag{5}(u'_n,w)+(Au_n,w)=(f,w), \ \forall \ w\in V_n$$

From $(5)$ we conclude that $$\tag{6}(Pu'_n,w)+(APu_n,w)=(f,P_nw),\ \forall w\in V_n$$

Note that (by definition) $(P_nf, w)=(f,P_nw)$, so by applying the same argument as in $(4)$ to the equation $(6)$ we conclude that $$(P_nu'_n)+(P_nAu_n,w)=(P_nf,w),\ \forall w\in V$$

From the last equality we conclude that $(3)$ is true.

II - $(2)$ implies $(1)$

Just apply $w_j$ in both sides and note that $(P_nf,w_j)=(f,P_nw_j)=(f,w_j)$.

  • $\begingroup$ I agree that $Au_n \in L^2(0,T;V')$, $u_n' \in L^2(0,T;V')$, and $f \in L^2(0,T;V')$. But why is true that $u_n' = Au_n + f$ in $L^2(0,T;V')$? I just don't understand why that equality holds. $\endgroup$ – workl Jun 25 '13 at 12:32
  • $\begingroup$ I am asking why adding $Au_n$ to $f$ equals $u_n'.$ $\endgroup$ – workl Jun 25 '13 at 12:34
  • $\begingroup$ @workl take a look and see if you get convinced now. $\endgroup$ – Tomás Jun 25 '13 at 13:02
  • $\begingroup$ Thanks for your help. I have to say I am still not sure.. remember equation (1) (in your post) holds in a weak sense only so it not that clear to me that you can just apply the projection operator like that. $\endgroup$ – workl Jun 25 '13 at 13:29
  • $\begingroup$ Applying the projection operator to $(1)$ is unnecessary for my conclusion (although it is valid). I have used it only as as heuristic point of view, beucase what I really want to show you was that $(2)$ is equivalently to $(3)$ and this is always true. $\endgroup$ – Tomás Jun 25 '13 at 13:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.